Apuração instantânea do documento de arrecadação do simples nacional: anexo i - comércio - MORAIS, Daniel Leandro; SANTANA, Herberto Vinicius de; FERRARI, Letícia Alves; FERRER, Paulo Enrique (031, 2019)
Empreendedorismo não é simplesmente abrir uma empresa, mas uma atitude que permite que uma dificuldade se transforme em uma oportunidade. O desemprego no Brasil apresenta índices alarmantes em 2019: dados divulgados pelo IBGE em maio indicam que a taxa de desemprego no Brasil, totalizam mais de 12 milhões de brasileiros sem trabalho no mês de setembro de 2019. Assim, o desemprego e a crise econômica no Brasil estão entre os principais fatores do aumento do empreendedorismo no Brasil, especialmente por necessidade. O objetivo do projeto é a criação de um software, simples, interativo e, que pode ser instalado como um aplicativo num aparelho celular, capaz de calcular o valor do imposto a recolher do Simples Nacional no mês subsequente ao do faturamento, instantaneamente, a cada venda realizada por uma empresa enquadrada no Anexo I – Comércio, da Lei Complementar 123/2006. ABSTRACT: "Entrepreneurship is not simply opening a company, but an attitude that allows a difficulty to become an opportunity. Unemployment in Brazil has alarming rates in 2019: data released by the IBGE in May indicate that the unemployment rate in Brazil totals more than 12 million Brazilians without work in the month of September 2019. Thus, unemployment and the economic crisis in Brazil are among the main factors in the rise of entrepreneurship in Brazil, especially out of necessity. The objective of the project is to create a simple, interactive software that can be installed as an application on a mobile device, capable of calculating the amount of tax payable by Simples Nacional in the month following the billing month, instantly, every sale made by a company included in Annex I - Commerce, of Complementary Law 123/2006."

Entrepreneurship is not simply opening a company, but an attitude that allows a difficulty to become an opportunity. Unemployment in Brazil has alarming rates in 2019: data released by the IBGE in May indicate that the unemployment rate in Brazil totals more than 12 million Brazilians without work in the month of September 2019. Thus, unemployment and the economic crisis in Brazil are among the main factors in the rise of entrepreneurship in Brazil, especially out of necessity. The objective of the project is to create a simple, interactive software that can be installed as an application on a mobile device, capable of calculating the amount of tax payable by Simples Nacional in the month following the billing month, instantly, every sale made by a company included in Annex I - Commerce, of Complementary Law 123/2006.
Instant calculation of the simple national collection document: annex i - commerce
Keywords: Empreendedorismo; Tributação; Gestão e Negócios